Kontekstualisasi Hadis Tentang Transplantasi - Lailatu Rohmah (STAI ALHIKMAH Jakarta, 2018)
Organ transplantation as a medical technique is a new improvement and discovery in the world of modern medicine. For example, the first successfully heart Transplantation was carried out in 1967. Until now many organs or tissues can be transplanted, including skin, cornea, bones, blood vessels, kidneys, heart, liver, lungs, and pancreas. While in the review of Islamic law, transplantation is a contemporary issue, and there are no texts in the Qur’an and Hadith that explicitly mentioning transplantation. Because of its increasing widespread of the organ transplants, it is regarded obligatory to study further in the Islamic perspective or Hadith on organ transplants. In this article, the author analyzes the Hadith relating to the transplants, then relates to the social context and various opinions of the scholars about organ transplants. Keywords: Contextualization Hadith, Transplantation Transplantasi organ sebagai teknik pengobatan merupakan kemajuan dan temuan baru dalam dunia kedokteran modern. Misalnya, Transplantasi jantung pertama kali sukses dilakukan tahun 1967. Hingga kini sudah banyak organ atau jaringan yang dapat ditransplantasikan, antara lain kulit, kornea, tulang, pembuluh darah, ginjal, jantung, hati, paru, dan pankreas. Sementara dalam tinjauan hukum Islam transplantasi ini merupakan masalah kontemporer, dan tidak ada nash al- Qur’an dan hadis yang secara eksplisit menyebutkan tentang transplantasi tersebut. Karena semakin maraknya transplantasi organ ini, maka dipandang perlu dikaji lebih jauh dalam perspektif Islam tentang transplantasi organ tersebut. Dalam artikel ini, penulis mengkaji hadis yang berkaitan dengan transplantasi, kemudian dikaitkan dengan konteks sosial serta berbagai pendapat ulama tentang transplantasi organ tubuh. Kata Kunci: Kontekstualisasi, Hadis, Transplantasi